Fatal Deliberate Self Harm with Paraquat - Majumder, Mohammed Ishaque; Hoque, Mohammad Mahfuzul; Ahmed, BUM Wahid; Rahman, AHM Walliur; Noor-E-Alam, Sheikh Mohammad; Faiz, Md Abul (Journal of Medicine, 2010)
Deliberate self harm using paraquat is a significant problem in parts of Asia, the Pacific and Caribbean. It is used as herbicide and highly toxic after ingestion. Large amount of paraquat leads to rapid death but smaller doses often cause a delayed lung fibrosis. A 21-yr-old female patient with paraquat poisoning with complaints of retrosternal and epigastric pain, mild respiratory distress and jaundice was admitted. She was icteric, her pulse was fast, subcutaneous emphysema was found at neck and lung was clear. Her respiratory distress, renal and liver function deteriorated and the patient was shifted to ICU and died on fourth day of poisoning. Methylprednisolone and cyclophosphamide pulse therapy was given but the patient died from multi-organ failure. Paraquat is very toxic and has no antidote. Keywords: Paraquat; gramoxone; herbicides; poisoning; Bangladesh DOI: 10.3329/jom.v11i2.5467 J MEDICINE 2010; 11 : 176-179